Teacher-led professional development through a model of action research, collaboration and facilitation. Issue 5 (20th October 2021) - Lambirth, Andrew; Cabral, Ana; McDonald, Roger; Philpott, Chris; Brett, Ashley; Magaji, Adewale
ABSTRACT: This article addresses the need for 'coherent, holistic frameworks offering insightful understandings as well as viable, connected and synergistic solutions to schools'. We describe a model which emerged from a research study developed in the context of a professional development course attended by more than 150 teachers from primary and secondary schools in Southeast London and Kent (UK) in the last 4 years. The design was based on data collected through 28 interviews to participants, reports and evaluation surveys and field notes from facilitators. The model is particularly innovative because it portrays not only the process of facilitation of action research but also the process of collaboration between facilitators and participants. It identifies five steps of development of teacher-led action research and highlights the issues and challenges to be considered in each step: 1. Defining the field of action (motivations and concerns, finding a research focus and questioning); 2. Planning (time, research skills and criticality); 3. Action (power relations and ethical awareness); 4. Evaluation (professional judgement, peer review, theory and practice) and 5. Reflection/(Re)planning (transformation and sustained development). This model can be used as a framework to enhance the development of teacher-led research in schools.